Expression of NLRP3 and AIM2 inflammasome in Peripheral blood in Chinese patients with acute and chronic brucellosis - Xiao Su; Shigang Zhao; Yijun Song (Scientific Reports, 2022)
Abstract Brucellosis is a zoonotic disease caused by Brucella abortus. An efficient immune response is crucial for curing brucellosis. The inflammasome plays a significant role in the immune response. It is unclear which inflammasome is active in acute and chronic brucellosis and how its levels relate to inflammatory cytokines. A total of 40 patients with acute or chronic brucellosis and 20 healthy volunteers had peripheral blood samples collected. The expression levels of AIM2, NLRP3, ASC, and Caspase-1 were determined by a real-time polymerase chain reaction from RNA and serum samples, and IL-1β, IL-18, and IFN-γ were measured by enzyme-linked immunosorbent assay. In the acute brucellosis group, AIM2 expression was significantly higher, while ACS expression was significantly lower than that of healthy volunteers. In patients with chronic brucellosis, AIM2 expression was significantly lower, while Caspase-1 expression was significantly higher than that of healthy volunteers. Serum IL-18 and IFN-γ levels were significantly higher in patients with acute brucellosis than in healthy controls. The IFN-γ level was also significantly higher in patients with chronic brucellosis than in healthy controls. The inflammasome responds differently in different stages of brucellosis. The inflammasome may be the site of action of immune escape in brucellosis.